Vancomycin-resistant enterococci - Kolář, Milan (Klinicka mikrobiologie a infekcni lekarstvi, 2018)
The review describes important bacterial pathogens, namely enterococci, focusing on their resistance to glycopeptides. Presented are the basic phenotypes and genotypes of vancomycin-resistant enterococci and options for antibiotic therapy of infections with their etio-logical role. At the same time, their prevalence in the Czech Republic is characterized based on data from the EARS-Net and studies available in the literature. Finally, potential approaches to preventing the spread of these dangerous multidrug-resistant bacteria are defined.
Keywords: Česká republika; Drug Resistance, Multiple, Bacterial; antibakteriální látky; Czech Republic; enterokoky rezistentní vůči vankomycinu; lidé; Vancomycin-Resistant Enterococci; grampozitivní bakteriální infekce; Anti-Bacterial Agents; Gram-Positive Bacterial Infections; Humans; mnohočetná bakteriální léková rezistence